Teaching-learning in youth and adult education and Bourdieu's theory of reproduction (Research, Society and Development, 2020)
The aim of this work was to present approximations between the teaching-learning process in the education of young people and adults and the theory of reproduction of the scholar Pierre Bourdieu. It is possible to observe that, through the concepts proposed by the author, there are reflexes in the EJA, however it can be detached from a reproduction, as through practices that consider its context and its learnings. Bourdieu and Passeron's theory of reproduction brings with it conceptual elements such as symbolic violence, cultural capital and arbitrary power that can contribute to the understanding of certain realities, in this case, the educational one and more specifically on Youth and Adult Education (EJA), considering that these students come from a contextual reality of their own, with socioeconomic characteristics that go beyond age issues and that can have consequences on teaching-learning, making this class of students undergo a reproduction.